2014
DOI: 10.1161/circulationaha.114.008779
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antipsychotic Use and Risk of Acute Myocardial Infarction

Abstract: R ecent evidence suggests that psychiatric patients may be at increased risk for cardiovascular events. Large community studies report that people with mental illnesses have a 2-to 5-fold greater risk of coronary heart disease and a 2-to 3-fold greater risk of cardiac mortality than the general population. [1][2][3] This increased risk might be explained by risk factors commonly noted in these patients, including smoking, obesity, and unhealthy lifestyles. 4-6 Clinical Perspective on p 243The association of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 47 publications
2
44
2
3
Order By: Relevance
“…Our findings of elevated risk for MI in short term APs users are also consistent with those from previous studies (Brauer et al, 2015;Lin et al, 2014;Pariente et al, 2012;Yu et al, 2016), where the incidence rate of MI has been found to be higher during the first two months of treatment, declining with longer exposure time and potentially related to AP tolerance and cross-tolerance (Lin et al, 2014;Yu et al, 2016). Another explanation for such possibility might be that the indication for which APs were prescribed (e.g., acute psychotic phase in schizophrenia) was associated with state dependent cardiovascular risk factors (e.g., agitation), which then being controlled (e.g., because of AP treatment) in later months.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings of elevated risk for MI in short term APs users are also consistent with those from previous studies (Brauer et al, 2015;Lin et al, 2014;Pariente et al, 2012;Yu et al, 2016), where the incidence rate of MI has been found to be higher during the first two months of treatment, declining with longer exposure time and potentially related to AP tolerance and cross-tolerance (Lin et al, 2014;Yu et al, 2016). Another explanation for such possibility might be that the indication for which APs were prescribed (e.g., acute psychotic phase in schizophrenia) was associated with state dependent cardiovascular risk factors (e.g., agitation), which then being controlled (e.g., because of AP treatment) in later months.…”
Section: Discussionsupporting
confidence: 93%
“…(Lin et al, 2014), finding the highest risk with amisulpiride (OR 5.65, 95% CIs 2.97-10.76). However, another study conducted by Sahlberg et al (2015) found that the incidence of major adverse cardiovascular events (comprised the first occurring nonfatal MI) was higher with use of levomepromazine (RR 3.80, 95% CIs to typical and atypical APs as previously reported (Huybrechts et al, 2012;Jackson et al, 2015;Wang et al, 2009), differences between typical and atypical agents were observed in one direct comparison (Vasilyeva et al, 2013) which found higher MI risk in people using atypical APs.…”
Section: Mechanismmentioning
confidence: 98%
“…In the study which analyzed blood level of the drug, an inverse relationship was found between religiosity and medication compliance (Borras et al 2007). Studies of patients with addictions, including between 357 and 1,726 subjects, were the largest sources of evidence for this review (Kelly et al 2011;Krentzman et al 2013;Lin et al 2014). These studies were based on a 12-step program for recovery from addiction, including spiritual elements; participation in this form of intervention apparently stimulated involvement of patients in religious activities.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…However, the use of either typical or atypical antipsychotic drugs is also a major risk factor (Fan et al, 2013). Although it has been well-documented that antipsychotics-induced metabolic side-effects, such as diabetes, obesity and dyslipidemia, can indirectly bring additional burden on cardiovascular system, there is substantial evidence that the drug use can also directly cause cardiotoxicity, including arrhythmia, myocarditis and cardiomyopathy (Citrome et al, 2013;Lin et al, 2014;Stroup et al, 2013). Despite the increased concern over antipsychoticinduced cardiovascular mortality, the underlying mechanism of action of antipsychotics on cardiovascular system remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%